2021
DOI: 10.3390/su13158622
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of the A-Double Vehicle Combinations If Introduced to a Line-Haul Freight Transport Network

Abstract: One of the solutions to improve the eco-efficiency of road freight transport is to combine existing transport modules into Longer and/or Heavier Vehicles (LHVs). The scientific and industrial communities have paid increasing attention to an LHV, known as the A-double combination, consisting of a tractor, two 13.5-m semitrailers, and a dolly converter. The present research contributes to the existing literature by developing a methodology based on a cost-benefit approach to quantify the effects of the A-double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This is unacceptable from the point of view of policies to encourage intermodal transport. This is because allowing LHVs can reduce road freight costs and, consequently, induce a shift from rail and water to road transport [31,99]. For example, Liimatainen et al [100] found that sharing rail freight transport decreased by 4% due to allowing LHVs.…”
Section: Allowing High-capacity Road Vehiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is unacceptable from the point of view of policies to encourage intermodal transport. This is because allowing LHVs can reduce road freight costs and, consequently, induce a shift from rail and water to road transport [31,99]. For example, Liimatainen et al [100] found that sharing rail freight transport decreased by 4% due to allowing LHVs.…”
Section: Allowing High-capacity Road Vehiclesmentioning
confidence: 99%
“…Inadequate pricing policies for road transport [31,39,40,[93][94][95] Lack of full rail liberalization [10,16,31,69,[96][97][98]] Allowing high-capacity vehicles [31,[99][100][101][102]133] Lack of incentive policies [11,13,14,[23][24][25][26]103] Lack of awareness programs [11,14,36,40,57,63,83]…”
Section: Regulations and Subsidies -Related Barriersmentioning
confidence: 99%
“…Hernández and Peeta [30] insisted that a higher degree of collaboration always leads to a win-win situation in a single-carrier collaboration problem when a less-than-truckload carrier seeks to acquire other carriers' capacity to service excess demand. Karam and Reinau [31] proposed a double combination to improve the eco-efficiency of road freight transport in empty tractor-semitrailer trips, but it is less effective for just-intime deliveries. Obviously, the algorithm optimization has achieved great benefits for enterprises, but with the development of the supply chain, the limitation of the enterprise's internal operation optimization becomes more obvious.…”
Section: Related Workmentioning
confidence: 99%
“…The number of affected trips in each route includes the first-affected trip and reactionary-affected trips. The CO2 emission of each trip is calculated following the method described in [32] which used the Passenger car and Heavy-duty Emission Model to estimate the CO2emission factors at different values of payload and speed. Linear interpolation and extrapolation were utilized to get the emission values at other payload values.…”
Section: B the Online Planning Modulementioning
confidence: 99%